STUDI MENGENAI BRAND LOYALTY DALAM MENINGKATKAN BRAND EQUITY KARTU PRABAYAR GSM PT. INDOSAT KOTA SEMARANG - Hasanah, Emy Yatul; Mudiantono, Mudiantono; Soesanto, Harry (JURNAL BISNIS STRATEGI, 2008)
Mobile phone industry is experiencing rapid growth in the last two decades, both in the developed countries or developing. In any mobile phone has changed the map of the telecommunications industry drastically. Various brands appear and compete closely. This raises the question "How Brand Image, Service Quality, Perceived Value into the very important for companies to establish and Brand Loyalty in the end to the increase in the Brand Equity", as in the theory and various journals and also whether there are PT in the telecommunications industry. Indosat is a problem that you want to be inspected in this research.Model studies indicate the existence of 4 (four) hypothetical. -Hypothetical hypothetical example is the brand image have a positive influence on brand loyalty (hypothetical 1), service quality has a positive influence on brand loyalty (hypothetical 2), the perceived value of a positive brand loyalty (hypothetical 3), brand loyalty and positive effect on brand equity (hypothetical 4).Sampling technique in this research carried out by purposively sampling method. This was taken with a sampling technique based on the specific considerations, where the sample is selected with the requirements that have deemed essential features that are relevant to the research. The number of respondents as the sample is determined in this research is 130GSM card customer PT. Indosat. The process of analysis of research carried out on data obtained from 130 respondents. Results of data analysis will be kausalitas explain the relationship between variables that are developed in this research model. The proposed model can be accepted after the assumptions have been met and that is normalitas standardized Residual Covariance <1.96. While the value Determinant of Covariance Matrixnya 102,358.Eksogen measurement model and endogen was tested by using analysis konfirmatori. Measurement model is further analyzed with Structural Equation Model (SEM) to test the model kausalitas relationship between the variables that affect and be affected by brand image, service quality, perceived value, brand loyalty and brand equity meet the Goodness of Fit chi square = 197437 ; probability = 0206; GFI = 0874; AGFI = 0840; cfi = 0995; TLI = 0994; RMSEA = 0026; CMIN / DF = 1085. Based on the results of data analysis can be concluded that the model can be accepted.